Structural and optical studies of tetra (tricarbethoxy)-substituted metallophthalocyanines - Sorar, Idris; Sener, M. Kasim; Tepehan, Fatma Z.; Gul, Ahmet; Kocak, M. Burkut (ELSEVIER SCIENCE SA, 2008)
Thin films of tetra (tricarbethoxy)-substituted metallophthalocyanines [where the metal was Cobalt(II), Copper(II) or Palladiurn(II)] were prepared by spin coating technique. Optical proper-ties of thin films were investigated by measuring the transmittance and reflectance using a spectrophotometer in the wavelength range of 350-1000 nm. The refraction index and extinction coefficient were determined. Surface microstructure of the films was observed by Atomic force microscopy. Also, the optical band gap and dielectric constant values were calculated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: phthalocyanine films; cobalt; copper; palladium; optical properties; structural properties; BAND-GAP; PHTHALOCYANINE; ENERGY; FILMS; Materials Science; Physics